STRATEGI PENGEMBANGAN KAWASAN PULAU PIEH DAN LAUT SEKITARNYA SEBAGAI TAMAN WISATA PERAIRAN(TWP) DI SUMATERA BARAT - Asep Syaiful Bahri (Sadar Wisata: Jurnal Pariwisata, 2019)
AbstractThe purpose of this research is to study the strategy of developing Tourism Tourism Waters (TWP) as an effort to develop the potential and natural wealth and culture of Indonesia in a sustainable manner, especially in the TWP area of Pieh Island and the Surrounding Sea in West Sumatra. The research method used in this research is descriptive method using SWOT analysis. The results of this study indicate that the pieh island TWP is in the category of growth which is focused on vertical integration. Where in these conditions the manager of the Pieh Island TWP must optimize tourism potential by integrating all potential and related stakeholders. Besides that, the TWP manager of Pieh Island and its surroundings delineates both in the water area and the island, so that any tourism activities that can be carried out in the Pieh Island and surrounding areas.